Religious Habituation Management: Autonomy vs Control in Vocational Schools - Agus Kusnandar; Iskandar Mirza (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study comparatively analyzes the management of Dhuha Prayer and Asmaul Husna Dhikr habituation programs in two vocational high schools: SMKN 12 Bandung and SMKS Angkasa Husein Bandung, to understand their effectiveness in shaping students' religious character. Employing a qualitative approach with a multi-site comparative design, the research explores how different organizational cultures and management models influence program outcomes. SMKN 12 Bandung utilizes a decentralized model, granting autonomy to students through Rohis, which fosters responsibility but struggles with attendance consistency and spiritual internalization depth due to dense practical schedules and minimal control. In contrast, SMKS Angkasa Husein Bandung implements a centralized, disciplinary model that ensures order and consistent attendance but risks creating ritualism and feelings of compulsion among students. The findings highlight that effective religious character formation requires a harmonious balance between external discipline and internal awareness. An optimal model should combine consistent implementation with mechanisms for deep reflection and student autonomy, avoiding scenarios where control without autonomy leads to superficial practice, or autonomy without control compromises quality. The study suggests tailored improvements for each school, emphasizing structured supervision for SMKN 12 and greater student initiative with richer religious content for SMKS Angkasa Husein.